Auditoría de Gestión del Gobierno Autónomo Descentralizado Parroquial Rural “El Esfuerzo”, Cantón Santo Domingo, Período 2020. - Valdivieso Oleas, Gioconda Elizabeth (2022)
The present research work entitled; MANAGEMENT AUDIT OF THE AUTONOMOUS DECENTRALIZED RURAL PARISH GOVERNMENT “EL ESFUERZO”, CANTON IN SANTO DOMINGO, DURING 2020, was developed with the purpose of applying the knowledge acquired in college concerning to the development of the Management Audit; which ais to evaluate the levels of efficiency, efficacy and economy with which the available resources are managed in the institution, measure the fulfillment of the goals and objectives set and evaluate the functioning of the internal control and institutional management. In order to reach the management audit, a previous visit to the institution was made, continuing with the review of information of the Autonomous Decentralized Rural Parish Government “El Esfuerzo”, which served to carry out the Preliminary Knowledge and Planning Phase, moreover information was collected through the visit previously made; consequently, to develop the specific objectives set, which were aimed at Evaluate the Internal Control System established in the entity, for which the internal control questionnaire was applied, which allowed to know the level of confidence and the level of risk in each of the components examined; then, it was proceeded to verify the degree of compliance with regulations and legal provisions during the development of the different projects, activities and works developed during the period examined and analyzed, then in the Execution Phase, the Efficiency indicators such as the budget, level of indebtedness, financial dependence were applied; Effectiveness indicators were applied to the knowledge of the mission, vision, objectives, trainings, evaluations to the personnel working in the entity, performance according to its title and executed projects; while among the Economy Indicators the personnel expenses, current expenses and investment expenses of the different plans and projects developed by the entity were applied; after having carried out the respective management audit in the entity, the audit report will be presented, which contains suggestions that will allow improving the administration of the institution.